Baseline characterization of the practices and use of fish feed ingredients among fish farmers processors in Nigeria - Manyise, Timothy; Ahmad Fatan, Nurulhuda; Olaniyi, Ajibola; Siriwardena, Sunil; Fregene, Bernadette; Yossa, Rodrigue; Rossignoli, Cristiano (2024)
This dataset includes information from 580 small-scale fish farmers, selected through a multistage sampling approach, to establish a baseline for the Development and Scaling of Sustainable Feeds for Resilient Aquatic Food Systems in Sub-Saharan Africa (FASA) project in Nigeria. Data was collected in April and May 2024 using a KoBo-based questionnaire administered via computer-assisted personal interviews (CAPIs) on mobile tablets by 20 trained enumerators. The dataset provides insights into the practices, challenges, and resource needs of small-scale fish farmers, offering a foundation for developing and scaling fish feed using local ingredients to support a resilient aquaculture sector in Nigeria. By capturing this data at the start of the project, it serves as a reference point for assessing progress and measuring the impact of future efforts to improve the resilience and sustainability of Nigeria's aquaculture industry. The data helps stakeholders, including policymakers and development partners, design targeted interventions that address the specific needs of small-scale fish farmers.